2021
DOI: 10.1016/j.ijcard.2021.05.029
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal apelin-ACE2 and SGLT2 signaling contribute to adverse cardiorenal injury in patients with COVID-19

Abstract: Background: Angiotensin converting enzyme 2 (ACE2) has recently been identified as the functional receptor for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the causative agent response for novel coronavirus disease 2019 . This study aimed to explore the roles of ACE2, apelin and sodium-glucose cotransporter 2 (SGLT2) in SARS-CoV-2-mediated cardiorenal damage. Methods and Results: The published RNA-sequencing datasets of cardiomyocytes infected with SARS-CoV-2 and COVID-19 patients were used. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The lower serum apelin levels found in COV patients in this study can be a result of its degradation by ACE2 as circulatory ACE2 has been shown to be increased in patients with COVID-19 [30]. In an animal model of ARDS, there was a significant decrease in the level of apelin in blood and lung tissue [29], and ACE2 and apelin expressions decreased in cardiomyocytes infected by SARS-CoV-2 [27].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The lower serum apelin levels found in COV patients in this study can be a result of its degradation by ACE2 as circulatory ACE2 has been shown to be increased in patients with COVID-19 [30]. In an animal model of ARDS, there was a significant decrease in the level of apelin in blood and lung tissue [29], and ACE2 and apelin expressions decreased in cardiomyocytes infected by SARS-CoV-2 [27].…”
Section: Discussionmentioning
confidence: 82%
“…Therefore, it is suggested that lower apelin levels may worsen COVID-19 disease complications. Apelin can exert its effect directly by binding to APJ and acting on several signaling pathways in different tissues, including the respiratory and circulation system, and indirectly by enhancement of ACE2 expression [27,28]. In experimental models of ARDS, apelin inhibits pro-inflammatory cytokine production, reduces inflammation, and improves oxygenation by activation of AKI-eNOS pathways [29].…”
Section: Discussionmentioning
confidence: 99%
“…50 Recent studies suggest possible beneficial effects of noninsulin antihyperglycemic agents against SARS-CoV-2 infection, such as dipeptidyl peptidase-4 inhibitors (DPP4i), sodium-glucose cotransporter-2 inhibitors (SGLT2i), and glucagon-like peptide-1 (GLP-1) receptor agonists. [51][52][53][54][55] The current study has several limitations: (i) more examinations with human ACE2-transgenic mice might be considered to confirm the conclusion of this study. (ii) This experimental model is limited with respect to pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
“…To update our knowledge, the levels of irisin are regarded to be an attribute of the management of T2DM and HF. For instance, previous clinical studies have shown some benefit in cardiac myocyte protection due to an SGLT2 inhibitor-related increase in serum levels of various adipomyokines, such as apelin and irisin, and a decrease in myostatin in HF [ 58 , 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%